Knowledge Analysis And Family Support On Diet Compliance In Patients With Chronic Kidney Failure In The Hemodialysis Room, Mayapada Surabaya Hospital - Alfian Fawzi; Adhyaksa Indrajid Putra; Aprin Rusmawati; Agusta Dian Ellina; M. Asad Effendy; Joko Sutrisno; Sismulyanto (Journal of Health Science Community, 2023)
Long enough hemodialysis reduces the patient’s enthusiasm for life so that it can affect adherence to the patient’s dietary requirements. Diet non-compliance is a big problem, especially in hemodialysis patients. The impact of non-compliance can affect the quality of life of clients, and increasing healthcare costs can also affect compliance in undergoing hemodialysis therapy. therefore family support factors greatly affect the level of dietary adherence in patients. To determine the relationship between the level of knowledge analysis and family support with dietary adherence in chronic kidney failure patients undergoing hemodialysis at Mayapada Hospital in Surabaya. This type of research is a quantitative descriptive study with a cross-sectional approach. Sampling technique with purposive sampling. The measuring tool in this study used a questionnaire. The data test used is the Logistic Regression Test. The results of the logistic regression analysis of knowledge and family support with dietary adherence showed a ρ-value of 0.143 and 0.132 respectively, which means there was no relationship between knowledge and family support with dietary compliance in patients undergoing hemodialysis at Mayapada Hospital. The conclusion is no relationship between knowledge analysis and family support with dietary adherence of patients undergoing hemodialysis at Mayapada Hospital. Education and counseling by health workers on the importance of family support in the form of instrumental support, informational support, emotional support, and appraisal support are needed.